The influence of managerial abilities of headmaster and teacher perceptions on teacher motivation at islamic junior high school 2 oku timur - Zaenal Arifin; Bukman Lian; Alhadi Yan Putra (Journal of Educational and Learning Studies, 2021)
The principal is a teacher who should have the ability to lead all resources in a school so that they can be maximally utilized to achieve common goals. Furthermore, the purpose of this study was to determine the effect of training and leadership style of the principal on the performance at Islamic junior high school 2 of OKU Timur district. This research was conducted in the world of education which focuses on schools, namely teachers of Islamic junior high school of Cempaka district. This research was conducted from June to September 2020. The data collection techniques used in this study included questionnaire methods, observation and documentation. Meanwhile, the respondents in this study were 60 teachers. The data analysis method used quantitative analysis, using the SPSS 21 application. The analysis carried out was the correlation analysis of the t test and the F test. The results of the data analysis from the questionnaire showed that there was an effect of training on the performance of Islamic junior high school 2 in Cempakasub district of OKU Timur district. Leadership on teacher performance at Islamic junior high school 2 in Cempakasub district of OKU Timur district. There is an effect of the Education and Training and Leadership Style jointly on the teacher performance at Islamic junior high school 2 in Cempakasub district of OKU Timur district